Federation Expulsions and Union Mergers in the United States - Chaison, Gary (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1973)
While the frequency of mergers among unions in the United States has only recently increased, mergers have played a major role in the affairs of unions expelled from federations (AFL, CIO and AFL-CIO) since 1949. An examination of the seventeen expelled unions indicates that only two have entirely disbanded and only one has returned directly to its federation. The remaining expelled unions merged with or into either their rival affiliates or other expelled unions. It is suggested that this high incidence of mergers was the results of the manner in which isolation induced exiles to merge while also reducing previously formidable barriers.